Evidence on the financing of industry and trade : Committee of Scottish clearing bankers Scottish Development Agency - Committee to review the functioning of financial institutions (London : Crown publications ; Her Majesty's Stationery Office, 1978)
This report covers the origin and growth of the Clearing Banks in Scotland and the Scottish economy.
Volume 6.
kjo 15/01/2019
Ref
Keywords: Finance; Industrialization -- Scotland; Financial institutions -- Scotland